Polarisation and health - Cristina Blanco Pérez; Xavier Ramos (Institute for the Study of Labor (IZA), 2008)
This paper examines the effect of income polarisation on individual health. We argue that polarisation captures much better the social tension and conflict that underlie some of the pathways linking income disparities and individual health, and which have been traditionally proxied by inequality. We test our premises with panel data for Spain. Results show that polarisation has a detrimental effect on health. We also find that the way the relevant population subgroups are defined is important: polarisation is only significant if measured between education-age groups for each region. Regional polarisation is not significant. Our results are obtained conditional on a comprehensive set of controls, including absolute and relative income.
urn:nbn:de:101:1-20081014326
Keywords: D31; 330; Polarisation; health; fixed-effects ordered logit model; conflict; psychosocial stress; social capital; Soziale Ungleichheit; Gesundheit; Einkommensverteilung; Sozialpsychologie; Social Capital; Spanien